Murder at the lanterne rouge ebook - Black, Cara (Aimee Leduc, 2012)
The twelfth Aimée Leduc investigation set in Paris Lost secrets of the Parisian Knights Templar, dangerous Chinatown sweatshops, dirty policemen, and botched affairs of the heart—the 12th Aimée Leduc mystery is the most exciting yet! Aimée Leduc is happy her longtime business partner René has found a girlfriend. It’s not her fault if she can’t suppress her doubts about the relationship. And her misgivings may not be far off the mark: Meizi disappears during a Chinatown dinner to take a phone call and never returns to the restaurant. Minutes later, the body of a young man, a science prodigy and volunteer at the nearby Musée, is found shrink-wrapped in an alleyway—with Meizi’s photo in his wallet. Aimée does not like this scenario one bit, but she can’t figure out how the murder is connected to Meizi’s disappearance. The dead genius was sitting on a discovery that has France’s secret service keeping tabs on him. Now they’re keeping tabs on Aimée. What has she gotten herself into? And can she get herself—and her friends—back out of it alive?